2021
DOI: 10.3390/ijms22179203
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Modulate the Epithelial-to-Mesenchymal Transition in Estrogen-Dependent Breast Cancer Cells In Vitro

Abstract: Silver nanoparticles (AgNPs) are frequently detected in many convenience goods, such as cosmetics, that are applied directly to the skin. AgNPs accumulated in cells can modulate a wide range of molecular pathways, causing direct changes in cells. The aim of this study is to assess the capability of AgNPs to modulate the metastasis of breast cancer cells through the induction of epithelial-to-mesenchymal transition (EMT). The effect of the AgNPs on MCF-7 cells was investigated via the sulforhodamine B method, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…In a recent study, it has been reported that AgNPs can regulate signaling pathways or can block tumor cell metastasis by inhibiting angiogenesis [ 89 ]. Rakowski et al [ 90 ] demonstrated that AgNPs can modulate the metastasis of MCF-7 breast cancer cells across the EMT pathway and can modify the metabolism of breast cancer cells by inducing reactive oxygen species (ROS) generation. Furthermore, Lee et al [ 91 ] have shown that the anticancer mechanism involves also the down-regulation of the antiapoptotic proteins, such as BCL-2, and upregulation of ROS, caspase 3 and P53 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it has been reported that AgNPs can regulate signaling pathways or can block tumor cell metastasis by inhibiting angiogenesis [ 89 ]. Rakowski et al [ 90 ] demonstrated that AgNPs can modulate the metastasis of MCF-7 breast cancer cells across the EMT pathway and can modify the metabolism of breast cancer cells by inducing reactive oxygen species (ROS) generation. Furthermore, Lee et al [ 91 ] have shown that the anticancer mechanism involves also the down-regulation of the antiapoptotic proteins, such as BCL-2, and upregulation of ROS, caspase 3 and P53 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ROS in the activation of EMT, through HIF1α stabilization, is still unclear, despite the involvement of ROS and HIF-1α in this process which has been highlighted by a number of authors [ 40 , 41 , 42 ]. This evidence was also supported by data showing that antioxidants, such as SkQR1, NAC, Mito-CP, and Mito-TEMPO, are able to modulate EMT [ 41 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 52%
“…A number of authors have reported the effect of antioxidants, such as SkQR1, NAC, Mito-CP, and Mito-TEMPO [ 41 , 43 , 44 ] on the redox modulation of EMT; however, the involvement of the mitochondrial Complex III UQCRB site in the EMT reversion, due to the inhibition of the hypoxia-induced mitochondrial ROS production and the related decrease in HIF-1α stabilization, represents the novelty of this work and might provide a rationale for the development of drugs able to counteract tumor progression induced by the EMT by blocking mitochondrial ROS production at this site.…”
Section: Discussionmentioning
confidence: 99%
“… 49 The specificities and function are dictated by the biochemical properties of the structure and their functional groups. Standard AgNPs are known to have cytotoxic properties in vitro, 50 but with green synthesis, therapeutic secondary plant metabolites surrounding the silver nucleus can lead to additional properties 51 and possibly a targeted approach that leads to selectivity towards certain types of diseased cells, broadening the safety index and the therapeutic implications of the treatment possibly contributing to precision medicine. Thus, it is reasonable to assume that it is the functional groups present in the secondary metabolites surrounding the NPs that dictate the cytotoxic activity, selectivity, and safety profile.…”
Section: Discussionmentioning
confidence: 99%